Association between inflammatory markers, BDNF, MCP-1 levels and insulin resistance in obese premenopausal women - Moushira Zaki (Journal of Global Pharma Technology, 2019)
The present study deals with the investigation of serum TNF-α, IL-6, brain derived neurotrophic factor (BDNF), monocyte chemo-attractant and protein1 (MCP-1), fasting glucose and serum insulin levels of apparently healthy Egyptian premenopausal obese  women and compared with healthy non obese control women. This study aimed to determine assoction between inflammatory markers, BDNF, MCP-1, obesity measures and insulin resistance (IR) risk. The study included 120 apparently healthy Egyptian women, 60 obese and 60 non- obese. IR has been estimated by the Homeostasis Model Insulin Resistance (HOMA-IR). Results showed marked elevation in inflammatory markers and MCP-1 in obese women than controls. Significant reduction of BDNF levels was observed in obese cases with significant negative correlations with obesity measures and HOMA-IR and positive relations with TNF-α and MCP-1. In conclusion our data demonstrated increase of inflammatory markers and MCP-1 as well as decrease of BDNF levels in obese women, suggesting that these biomarkers might be positional candidate linking obesity markers that play important role for development of IR in apparently healthy Egyptian obese premenopausal women.